Duodenal localization is a negative predictor of survival after small bowel adenocarcinoma resection: as population-based, propensity score-matched analysis - Wilhelm, Alexander; Galata, Christian; Warschkow, René; Post, Stefan; Marti, Lukas (Journal of surgical oncology, 2018)
Background and Objectives This study assessed the influence of tumor localization of small bowel adenocarcinoma on survival after surgical resection. Methods Patients with resected small bowel adenocarcinoma, ACJJ stage I-III, were identified from the Surveillance, Epidemiology, and End Results database from 2004 to 2013. The impact of tumor localization on overall and cancer-specific survival was assessed using Cox proportional hazard regression models with and without risk-adjustment and propensity score methods. Results Adenocarcinoma was localized to the duodenum in 549 of 1025 patients (53.6%). There was no time trend for duodenal localization (P = 0.514). The 5-year cancer-specific survival rate was 48.2% (95%CI: 43.3-53.7%) for patients with duodenal carcinoma and 66.6% (95%CI: 61.6-72.1%) for patients with cancer located in the jejunum or ileum. Duodenal localization was associated with worse overall and cancer-specific survival in univariable (HR = 1.73; HR = 1.81, respectively; both P < 0.001), multivariable (HR = 1.52; HR = 1.65; both P < 0.001), and propensity score-adjusted analyses (HR = 1.33, P = 0.012; HR = 1.50, P = 0.002). Furthermore, young age, retrieval of more than 12 regional lymph nodes, less advanced stage, and married matrimonial status were positive, independent prognostic factors. Conclusions Duodenal localization is an independent risk factor for poor survival after resection of adenocarcinoma.